Beaver Dreaming and Singing - Ridington, Robin (Anthropologica, 2022)
Beaver Indian culture contains the vision quest and a semi-messianic prophet cult, but Beaver Indians are not familiar with the relevant literature and hence are unaware of these facts. What they know about is dreaming and singing and much of which we, being unfamiliar with the relevant non-literature, are unaware. Dreams present symbols that bridge from the unconscious to the superorganic, and songs are a medium through which the symbols touch resonances between subjectivities. The vision quest becomes an initiation when its meaning is dreamed and a song given. The prophet’s initiation is death and his songs are the road to heaven.